The great Godden - Rosoff, Meg 1956- (Bloomsbury, 2020)
This is the story of one family, one dreamy summer - the summer when everything changes. In a holiday house by the sea, in a big, messy family, one teenager watches as brothers and sisters, parents and older cousins fill hot days with wine and games and planning a wedding. Enter the Goddens - irresistible, charming, languidly sexy Kit and surly, silent Hugo. Suddenly there's a serpent in this paradise - and the consequences will be devastating. This is a lyrical and quintessential coming-of-age tale - a summer book that's as heady, timeless and irresistible as Bonjour Tristesse and I Capture the Castle but as sharp and fresh as Normal People